A retrospective analysis of mandibular grafting using vascularised free fibula flaps at the Charlotte Maxeke Johannesburg Academic Hospital - Hira, P.G. (My University, 2019)
Introduction: Segmental mandibular defects following significant maxillofacial trauma and ablative tumour surgery often present reconstructive challenges from the resultant mandibular bone and soft tissue defects. The volume of bone and soft tissues lost often necessitates composite microvascular flap reconstruction to be able to optimally rehabilitate these patients. Vascularised free fibula flaps have the concomitant benefit of providing adequate bone and soft tissue coverage. Aims and objectives: The aims are to retrospectively evaluate the reconstructive outcomes of vascularised mandibular free fibula flaps and to identify factors associated with favourable and unfavourable outcomes. Methods and materials: Patients with vascularised free fibula flaps to the mandible were included in the study. Data collected was divided into various categories, namely, demographic details, defect aetiology, the number of segments in the fibula, adjunctive radiation therapy, the subsequent immediate or delayed placement of dental implants and associated complications. Results: Twenty patients (8 males and 12 females) were included in this study. The most common aetiology of mandibular defects was neoplasia. The overall complication rate was 40% and ranged from graft loss due to anastomosis failure to dehiscence and minor sepsis. No significant association was found between gender, aetiology of defect, radiation therapy and reconstructive outcome. Nine patients subsequently received dental implants. Conclusion: There was a 90% fibula graft success rate. A larger sample size and a longer follow-up in a multidisciplinary team is needed to assist in the development of a better treatment and follow-up protocol in patients treated with vascularised free fibula flap.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Dentistry (MFOS)